Dental Treatment of a Child with Pallister-Killian Syndrome - Serhan Didinen; Didem Atabek; Gülay Kip; Aslı Patır Münevveroğlu; Özlem Tulunoğlu (Case Reports in Dentistry)
The Pallister-Killian syndrome (PKS) is an extremely rare genetic disorder with an incidence estimated around 1/25000. PKS is a multiple congenital anomaly deficit syndrome caused by mosaic tissue limited tetrasomy for chromosome 12p. The presented report is the first confirmed case with PKS in Turkey. This report focuses on the orofacial clinical manifestations of an 6-year-old boy with PKS who was referred to the Department of Paediatric Dentistry clinic, Gazi University. It has been learned that the PKS was diagnosed 1 year after birth. Due to intellectual disability, it was decided to make the dental treatments under moderate sedation. Although significant tongue thrust and anterior open bite were determined, any oral appliances could not be applied because of the 2 epilepsy seizures in the last 2 years. The aim was to treat decayed teeth and set good oral hygiene in the patient’s mouth. Still, there is a probability for epilepsy seizures. If epileptic seizures stop permanently, we can apply an oral appliance to block tongue thrust. The patient is now under control. In cases of systemic and oral findings such as PKS, conducting medical and dental approaches together will increase the life quality of patients.